PENGUATAN KARAKTER BISNIS BAGI PENGRAJIN PERABOT RUMAH TANGGA DARI KALENG BEKAS DI MONJOK KOTA MATARAM - Nururly, Santi; Suryatni, Mukmin; Burhanudin, Burhanudin; Sulaimiah, Sulaimiah; Rakhmawati, Intan (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Monjok Village, which is located in Mataram City, is a location known as an area that produces household appliances, such as ovens, small or large steamers, satay grills, cake makers, large spoons, graters, and various other kitchen utensils. The purpose of the service is to provide training in strengthening entrepreneurial character, efficient production training, marketing training, and basic bookkeeping, so that the business can develop further. The method used is training. The service activity was carried out on October 4, 2024. After the service activity, an evaluation was still carried out to review the effectiveness of the training for the women craftsmen. Through this activity, it is hoped that the women craftsmen of household furniture can develop their businesses through better production, marketing, and business management.